Comparative analysis of impedance and time-domain protection in HVAC and HVDC interconnected systems: A case study in Colombia - Alejandra Garzón; David Celeita; Gustavo Ramos; Marc Petit; Trung Dung Le; Juan Pablo Hoyos; Alexandre Bach (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
High Voltage Alternating Current (HVAC) and High Voltage Direct Current (HVDC) systems are essential for effective energy transition and electrification, introducing significant challenges in ensuring the reliability and security of power networks. This paper presents a comprehensive comparative analysis of impedance-based and time-domain protection schemes in the context of HVAC and HVDC interconnected systems. A case study in the diverse and challenging grid environment of Colombia serves as the backdrop for this research. Different fault scenarios were tested using COMTRADE files, revealing important insights when comparing impedance protection and traveling wave approaches, to highlight the strengths and weaknesses of both protection approaches. A key finding of this study is the identification of a potential vulnerability when relying solely on alternating current side protection for faults on the direct current side. The results demonstrate that protection schemes based on incremental values or voltage memory can yield unreliable results, particularly in scenarios involving power swings and rapidly changing fault conditions (influenced by factors such as magnitude, trajectory, and rate of change). These insights underscore the importance of using more robust, multi-dimensional protection strategies in interconnected systems.